2014
DOI: 10.54652/rsf.2014.v44.i2.99
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Crataegus Monogyna L. Fruit Extracts

Abstract: UDK: 547.56:582.711.714           582.711.714:581.47 The aim of this work was to determine the content of total polyphenols, total flavonoids, total monomeric anthocyanins, total proanthocyanidins, and antioxidant activity of Crataegus monogyna L. fruit in water, hydroalcohol and alcohol extracts. Phenolic content and antioxidant assay of the different fruit extracts was determined using spectrophotometric methods. Obtained results indicated that the content of total polyphenols in the investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…According to Table 2, the TAC in CM extracts exhibited a range of values from 7.82 to 51.83 µg cyanidin equivalents (CyE)/g dw, ensuring a 562.79% increase. This result aligns perfectly with previous results, where TAC ranges from 0.004 to 0.132 mg CyE/g (i.e., 4 to 132 µg CyE/g) [42]. Following the optimum extraction parameters: 75% v/v ethanol solvent for 85 min extraction time at 80 • C presented in Table 4, the maximum TAC can be obtained around 55.47 µg CyE/g.…”
Section: Tpc and Tac Of The Extractssupporting
confidence: 91%
“…According to Table 2, the TAC in CM extracts exhibited a range of values from 7.82 to 51.83 µg cyanidin equivalents (CyE)/g dw, ensuring a 562.79% increase. This result aligns perfectly with previous results, where TAC ranges from 0.004 to 0.132 mg CyE/g (i.e., 4 to 132 µg CyE/g) [42]. Following the optimum extraction parameters: 75% v/v ethanol solvent for 85 min extraction time at 80 • C presented in Table 4, the maximum TAC can be obtained around 55.47 µg CyE/g.…”
Section: Tpc and Tac Of The Extractssupporting
confidence: 91%
“…Coklar et al (2018) determined the total phenolic content in fresh hawthorn fruit belonging to C. orientalis species as 13.36 mg GAE/g DW. Tahirović and Bašić (2014) determined the total phenolic content of the fruit between 2.02 and 4.60 mg GAE/g FW in the extraction they carried out for C. monogyna L. using different ratios of water and different solvents (water, ethanol, methanol). It is observed that the phenolic yield generally increases in extractions where organic solvents are mixed with water in certain proportions (Spigno et al, 2007).…”
Section: Total Phenolic Contents Phenolic Profile and Antioxidants Ca...mentioning
confidence: 99%